2018
DOI: 10.1515/pac-2017-0805
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and ionic conductivity of siloxane based polymer electrolytes with pendant propyl acetoacetate groups

Abstract: Hydrosilylation reaction of 2.4.6.8-tetrahydro-2.4.6.8-tetramethylcyclotetrasiloxane (D4H) with allyl acetoacetate at 1:4.1 molar ratios of initial compounds in the presence of platinum hydrochloric acid (0.1 M solution in THF), Karstedt’s catalyst (Pt2[(VinSiMe2)2O]3) and platinum on the carbon have been carried out and D4R type compounds obtained. Reaction order, rate constants and activation energies for hydrosilylation reactions in the presence of Karstedt’s catalyst have been determined. Ring-opening poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Further, the reaction of compounds containing epoxy groups with primary and secondary amines was carried out, and the corresponding compounds containing aminohydroxyl groups were obtained. Similarly, a linear methylsiloxane oligomer with regular arrangement of propyl acetoacetate groups in the side chain has been obtained [149]. In this work, the possibility of revealing epoxy groups is open to question; however, the authors confirm the composition and structure of the obtained compounds according to elemental analysis, such as FTIR, and 1 H, 13 C, and 29 Si NMR spectrum.…”
Section: Catalytic Rearrangement Reactions For the Preparation Of Pdm...mentioning
confidence: 79%
“…Further, the reaction of compounds containing epoxy groups with primary and secondary amines was carried out, and the corresponding compounds containing aminohydroxyl groups were obtained. Similarly, a linear methylsiloxane oligomer with regular arrangement of propyl acetoacetate groups in the side chain has been obtained [149]. In this work, the possibility of revealing epoxy groups is open to question; however, the authors confirm the composition and structure of the obtained compounds according to elemental analysis, such as FTIR, and 1 H, 13 C, and 29 Si NMR spectrum.…”
Section: Catalytic Rearrangement Reactions For the Preparation Of Pdm...mentioning
confidence: 79%
“…Siloxanes can not only serve as solvents but also as electrolyte additives which could participate in the interfacial film forming processes at both cathode and anode surfaces. [ 80–83 ] It was reported that the thermal stability of cathode charged in the siloxane electrolyte was superior to that in the carbonate‐based electrolyte. [ 84 ] Siloxane electrolytes were also demonstrated particularly suitable for carbonaceous electrode materials by forming a passive film at the electrode/electrolyte interface.…”
Section: Overview Of Organosiliconmentioning
confidence: 99%
“…Thus, polyorganosiloxanes with a regular arrangement of the side donor groups can be obtained. 11,12 As expected, the properties of the comb-type organosilicon polymers depend on the structure of macromolecular chains and on the nature of the organic groups surrounding the silicon atom. 8 In the comb-type copolymers, there are organic substituent groups of different sizes and types bonded to the methylsiloxane hydrophobic matrix.…”
Section: Introductionmentioning
confidence: 66%
“…overlaps with the signals of methine groups, 3.8 (m, Si-O-CH 2 ), 4.5 (t, CH 2 -CF 2 ), 5.95-5.61 (t, CF 2 H). 13 12,14,15 The hydrosilylation reactions in the presence of other catalysts were carried out in accordance with the same method.…”
Section: Hydrosilylation Reaction Of D4 H With 2233-tetrafluoropromentioning
confidence: 99%